The Impact of Swimming Training on the Course and Symptoms of Bronchial Asthma and Respiratory System Function: A Literature Review - Ptak, Anita; Szyc, Michał (Quality in Sport, 2024)
Introduction: Bronchial asthma is one of the most common inflammatory diseases among adults and children. It is characterized by the occurrence of bronchial obstruction, which is manifested, for instance, by a feeling of shortness of breath, wheezing, a feeling of tightness in the chest, a feeling of squeezing in the chest. In addition to pharmacological treatment, health behavior including sport is of great importance. In this publication, we will attempt to discuss the effects of swim training on asthma and respiratory system function. We will try to answer the question whether swimming is a safe form of exercise for patients with bronchial asthma. Material and methods: Review of the specialized literature in the field of pulmonology, guidelines for treatment of bronchial asthma and articles available on PubMed and Google Scholar database searching by the keywords Aim of the study: The aim of this publication is to review the available literature to answer the question of whether swimming training is a suitable form of exercise for asthmatic patients and what effect it has on respiratory function Conclusions: The treatment of bronchial asthma is based on the pharmacological treatment. In addition to medications, non-pharmacological methods and health behaviours are important. Appropriate physical activity for people with asthma may include swimming training, which has a beneficial effect on lung function and asthma symptoms management, especially in the paediatric population. There are studies that suggest that swimming carries a lower risk of causing bronchospasm than other sport activities, however, there are inconclusive reports on the effect of attending chlorinated swimming pools on the development of asthma and allergies. Studies on competitive and elite swimmers show that intensive swimming training, especially in chlorinated pools, can induce bronchial hyperresponsiveness and the risk of developing asthma, but this requires further research.